EFEKTIVITAS PENGGUNAAN METODE PEMBELAJARAN OUTDOOR DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 3 SD NEGERI 54 BANDA ACEH - Mira Destiana; Helminsyah; Haris Munandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of using the outdoor learning method in increasing the learning motivation of third-grade students at SD Negeri 54 Banda Aceh in the subject of IPAS (Integrated Science and Social Studies). The background of this study is the low level of students’ learning motivation caused by less engaging, monotonous, and unvaried teaching methods. The outdoor learning method is a teaching strategy conducted outside the classroom by utilizing the surrounding environment as a learning resource, allowing students to directly observe and interact with learning objects, particularly ecosystem materials. This research employed a quantitative method with a pre-experimental one-shot case study design involving third-grade students selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and documentation. The instruments were tested for validity and reliability using SPSS version 25. The conceptual framework was based on the assumption that the outdoor method can overcome students’ boredom in classroom learning by creating a more flexible, enjoyable, and concrete learning experience. The results showed that the outdoor learning method was effective in increasing students’ learning motivation, as indicated by improvements in enthusiasm, participation, and students’ ability to understand the material. Supporting factors included easily accessible learning media, more enjoyable learning activities, and concrete learning resources that facilitated better comprehension of the material. This study contributes theoretically to the development of educational science and practically provides teachers with an alternative creative teaching method to improve the quality of IPAS learning in elementary schools